2017
DOI: 10.25081/josac.2017.v26.i1.808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intercrops on growth and yield of turmeric (Curcuma longa L.)

Abstract: The initial growth of turmeric is rather slow and takes about 4-5 months to cover the inter space. Therefore, the available space between the rows of turmeric could be effectively utilized by growing short duration crops like, vegetables, cereals etc. Hence, it is worthwhile to explore the possibilities of growing compatible crops with turmeric. With this background the experiment on effect of intercrops on growth and yield of turmeric was conducted at Agricultural Research Station, Bhavanisagar. Among the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Application of vermicompost along with biofertilizers inoculation enhances the accumulation of higher quantities of seed constituents like carbohydrates, proteins as enzymes which increased the seedling vigour index of bolder seeds that contain greater meatbolites for resumption of embryonic growth during germination (Yadav and Khurana, 2005). These results are in conformity with Naimuddin et al (2014), Kumar and Sharma (2014) and Anitha et al (2016) in fenugreek and Thangaraj et al (2015) also presented similar findings. The results of seed quality (Table 2) showed that germination (%) was at par among the treatment combinations of vermicompost and biofertilizers.…”
Section: Resultssupporting
confidence: 91%
“…Application of vermicompost along with biofertilizers inoculation enhances the accumulation of higher quantities of seed constituents like carbohydrates, proteins as enzymes which increased the seedling vigour index of bolder seeds that contain greater meatbolites for resumption of embryonic growth during germination (Yadav and Khurana, 2005). These results are in conformity with Naimuddin et al (2014), Kumar and Sharma (2014) and Anitha et al (2016) in fenugreek and Thangaraj et al (2015) also presented similar findings. The results of seed quality (Table 2) showed that germination (%) was at par among the treatment combinations of vermicompost and biofertilizers.…”
Section: Resultssupporting
confidence: 91%
“…In terms of the amount of MOF, the collected data showed that the treatment with 6 tons MOF achieved the highest average actual fresh yield of 23.3 tons/ha, which was statistically significant for the control treatment. These result was in concordance with the study of Banwasi & Singh (2010) that the application of 100 and 150 kg P 2 O 5 /ha recorded the highest red turmeric yield growing in light clay soil, with the increasing level of phosphorus up to 200 kg/ha, the yield of red turmeric was tended to decrease. Besides, the study results of Padmapriya & Chezhiyan (2009) prevailed the effect of fertilizers (organic,…”
Section: Effects Of Micro-organic and Phosphorus Fertilizers On Yield...supporting
confidence: 92%
“…When auxins are more, the plants are able to absorb and translocate the nutrients to the apical bud. This leads to the conclusion that auxins act on some protoplasmic system leading to altered arrangement of cell wall components and hence greater extensibility leading to increased height" [10].…”
Section: Resultsmentioning
confidence: 99%